ULK1 phosphorylates Mad1 to regulate spindle assembly checkpoint - Yuan, Fengjie (Nucleic Acids Res, 2019)
The spindle assembly checkpoint (SAC) ensures the fidelity of chromosome segregation during mitosis. Here, we show that ULK1, a serine/threonine kinase that plays a key role in initiation of autophagy, also has an important function in the activation of SAC. ULK1 phosphorylates the SAC protein Mad1 at Ser546 to recruit Mad1 to kinetochores. Furthermore, Rod/ZW10/Zwilch (RZZ) complex may serve as a receptor for phos-Ser546-Mad1 at kinetochore, since phosphorylation of Mad1 by ULK1 strengthens the interaction between Mad1 and RZZ complex. In addition, deletion of ULK1 increases chromosome instability and cytotoxicity of paclitaxel, resulting in significant impairment of cancer cell growth. These findings highlight the role of ULK1 as a protein kinase controlling the fidelity of chromosome segregation and cell-cycle progression.